Mathematical proposals in classroom and in a non-formal science education context - Nogueira, Sofia (2012)
This paper presents results from a research on Didactics that aims to develop, produce, implement and evaluate the impact of the exploitation of interactive modules on science, on the development of problem solving and mathematical communication skills, of pupils (aged 9 or 10) attending the 4th grade of elementary school. Data suggests that the situations proposed had impact on the mathematical skills evaluated (strong on mathematical communication and weak on problem solving) and that the class evolved its skills in all moments of problem solving but not in every aspect of mathematical communication, identified from literature review.